الإنتاج المعرفي السوسيولوجي للأستاذ الجامعي ودوره في بناء الهوية التنظيمية - مسعودة عويسات (Universty Of El-oued جامعة الوادي, 2026)
هدفت الدراسة الموسومة بـ:" الإنتاج المعرفي السوسيولوجي للأستاذ الجامعي ودوره في بناء الهوية التنظيمية للجامعة" إلى محاولة الكشف عن طبيعة الإنتاج المعرفي السوسيولوجي للأستاذ الجامعي وكيف يساهم ذلك في بناء الهوية التنظيمية وفق الأبعاد المتمثلة في التميز والمركزية والاستمرارية، وقد أجريت الدراسة خلال السنة الجامعية 2020/2024 بجامعات الوادي وورقلة وغرداية على عينة من أساتذة علم الاجتماع في الجامعات المذكورة مكونة من 100 مفردة تم اختيارها بطريقة قصدية، وتم مسحها بشكل شامل لكل القسم، أمّا أدوات جمع البيانات فقد تمثلت في الاستمارة كأداة أساسية إضافة إلى الملاحظة والمقابلة كأدوات مساعدة. يمكن تلخيص نتائج الدراسة في النقاط الآتية: تنوع الإنتاج المعرفي السوسيولوجي للأستاذ الجامعي بين المقالات والتظاهرات العلمية كالملتقيات والأيام الدراسية والورشات والندوات العلمية ويمكن القول أنّ الملتقيات كانت أبرز تظاهرة علمية يشارك فيها الأستاذ الجامعي، بالإضافة إلى إنتاج الكتب واعتماد الدروس على الخط وكذلك تحويلها إلى مطبوعات بيداغوجية وعليه فأنّ طبيعة الإنتاج المعرفي السوسيولوجي متنوعة لكنها تعاني من نوعيتها وكميتها. يساهم الإنتاج المعرفي السوسيولوجي في بناء الهوية المتفردة للجامعة من خلال تسهيل إجراءات النشر، وتوفير مخابر البحث السوسيولوجي وتشجيع الأساتذة على إتقان اللغات الأجنبية وإتاحة فرص التكوين للأساتذة بالخارج وبناء إنتاج معرفي متكامل، وإبرام اتفاقيات مع جامعات وطنية ودولية. يساهم الإنتاج المعرفي السوسيولوجي في بناء الهوية المركزية للجامعة وذلك من خلال ما يميز المناخ التنظيمي وعلاقة الجامعة بالسلطة العليا ومواكبتها لتطورات الواقع الاجتماعي وتماثل أهدافها مع أهداف الفاعلين فيها. على ضوء ما تقدم من بيانات وعرض وتفسير فإنه يمكن القول أنّ طبيعة الإنتاج المعرفي السوسيولوجي للأستاذ الجامعي تساهم في بناء الهوية التنظيمية للجامعة وذلك من خلال نوعية هذا الإنتاج وغزارته. The study entitled “The Sociological Knowledge Production of the University Professor and Its Role in Building the Organizational Identity of the University” aimed to explore the nature of sociological knowledge production among university professors and how it contributes to building organizational identity according to its dimensions: distinctiveness, centrality, and continuity. The study was conducted during the academic year 2020–2024 at the Universities of El Oued, Ouargla, and Ghardaia on a purposive sample of 100 sociology professors from the aforementioned universities. A comprehensive survey was carried out for each department. The primary data collection tool was the questionnaire, supported by observation and interviews. The findings of the study can be summarized as follows: The sociological knowledge production of university professors varied between scientific articles and academic events such as conferences, study days, workshops, and scientific seminars. Conferences were identified as the most prominent academic activity in which professors participated, in addition to authoring books, delivering online courses, and transforming course materials into pedagogical publications. Thus, it can be said that although the nature of sociological knowledge production is diverse, it suffers from issues related to its quality and quantity. Sociological knowledge production contributes to building the university’s distinctive identity by facilitating publication procedures, providing sociological research laboratories, encouraging professors to master foreign languages, offering training opportunities abroad, developing an integrated body of knowledge, and establishing agreements with national and international universities. Sociological knowledge production also contributes to building the university’s central identity through characteristics related to the organizational climate, the university’s relationship with higher authorities, its responsiveness to social developments, and the alignment of its goals with those of its actors. In light of the presented data, analysis, and interpretation, it can be concluded that the nature of sociological knowledge production among university professors contributes to building the university’s organizational identity through the quality and abundance of this production.
أطروحة دكتوراه تخصص علم اجتماع التنظيم والعمل في العلوم الاجتماعية والإنسانية
Keywords: الإنتاج المعرفي السوسيولوجي، الهوية التنظيمية، الجامعة، الهوية المتفردة، الهوية المركزية.; Sociological knowledge production; organizational identity; university; distinctive identity; central identity